Assessing sea turtle, seabird and shark bycatch in artisanal, semi-industrial and industrial of fisheries in the Cabo Verde Archipelago - Montrond, Gilson (FitzPatrick Institute of African Ornithology, 2021)
Firstly, I am very grateful to Birdlife International for the MSc scholarship. I am also very grateful to Professor Peter Ryan of the FitzPatrick Institute of African Ornithology, University of Cape Town, for agreeing to supervise this project and for his guidance, insights and comments on the write-up. I am grateful to Sarah Saldanha, for all the support during this MSc. Many thanks also to Dr Ross Wanless, Dr Rima Jabado and Ruben Rocha for all support, guidance and advice. I want to thank a lot Andy Angel for their accommodation and all support in South Africa. I am grateful to all the UCT staff and BirdLife Senegal Staff for all the support during this study. Many thanks to my family for all the encouragement and support. I want to thank to all the Cabo Verde fishers for their willingness to share their knowledge and experience. Finally, many thanks to the Conservation Biology class of 2019, for all their support.